Evaluation and optimization of SYBR Green real-time reverse transcription polymerase chain reaction as a tool for diagnosis of the Flavivirus genus in Brazil - Marilia Farignoli Romeiro; William Marciel de Souza; Aline Lavado Tolardo; Luiz Carlos Vieira; Tatiana Elias Colombo; Victor Hugo Aquino; Maurício Lacerda Nogueira; Luiz Tadeu Moraes Figueiredo (Revista da Sociedade Brasileira de Medicina Tropical, 2016)
Abstract: INTRODUCTION: The genus Flavivirus includes several pathogenic species that cause severe illness in humans. Therefore, a rapid and accurate molecular method for diagnosis and surveillance of these viruses would be of great importance. Here, we evaluate and optimize a quantitative real-time reverse transcription polymerase chain reaction (RT-PCR) method for the diagnosis of the Flavivirus genus. METHODS: We evaluated different commercial kits that use the SYBR Green system for real-time RT-PCR with a primer set that amplifies a fragment of the NS5 flavivirus gene. The specificity and sensitivity of the assay were tested using twelve flaviviruses and ribonucleic acid (RNA) transcribed from the yellow fever virus. Additionally, this assay was evaluated using the sera of 410 patients from different regions of Brazil with acute febrile illness and a negative diagnosis for the dengue virus. RESULTS: The real-time RT-PCR amplified all flaviviruses tested at a melting temperature of 79.92 to 83.49°C. A detection limit of 100 copies per ml was determined for this assay. Surprisingly, we detected dengue virus in 4.1% (17/410) of samples from patients with febrile illness and a supposedly negative dengue infection diagnosis. The viral load in patients ranged from 2.1×107to 3.4×103copies per ml. CONCLUSIONS: The real-time RT-PCR method may be very useful for preliminary diagnoses in screenings, outbreaks, and other surveillance studies. Moreover, this assay can be easily applied to monitor viral activity and to measure viral load in pathogenesis studies.